Edukasi Pemeriksaan Inspeksi Visual As etat (IVA) dalam Meningkatkan Partisipasi Wanita Usia Subur - Rochmaniah, Dwi Ardani; Anggraini, Anita Dewi; Windarena, Diyas (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Cervical cancer is one of the most feared dissease among woman and can rank as the number one most deadly disease, especially when accompanied by other comorbidities. This dissease affects the female reproductive organ in cervix area and is caused by the human papilloma virus (HPV). Prevention efforts for cervical cancer can be carried outthrough Visual Inspection with Acetic Acid (VIA) screening, particularly for woman of reproductive age who are sexually active. In initial monitoring, it was found that 91.7% of respondents had neverundergone VIA Screening.  Objective: to evaluate the participation of women in early detection screening for cervical cancer in Pakunden Village, Ponoorogo Regency. Method: VIA Screening education was provided to 12 womenof reproductive age, targeting mothers/ women with toddlers who actively seechealth information by attending POSYANDU (community health services. Result: After providing education about the VIA Screening, there was an increase in the respondents’ willingness to participate in VIA examination.